Assessment of Efficiency of Retrobulbar Infusion of Neurometabolic Preparations in Increase of Hemodynamic of Optic Nerve at Acute Ischemic Optic Neuropathy - V. V. Egorov; L. P. Emanova; L. P. Danilova; G. P. Smoliakova (Oftalʹmologiâ)
Purpose. To study hemodynamic of optic nerve (ON) in process of complex pathogenetic direct treatment in patients with anteriorischemic optic neuropathy (AION). Patients and methods. 43 patients with acute phase AION were exanimated and treated. Besides the functional results (visual acuity, visual field), the diagnosis AION was based on indicators of ophthalmologic and angiographic researches of ON. Patients were divided into two groups. 23 patients were in the main group. They received neurometabolic medicinal preparations (MP) through a silicone retrobulbar catheter. The control group consisted of 20 patients who had the traditional method of medicines injection. Indexes of hemodynamic were estimated according to Doppler ultrasound of local blood flow at the short posterior ciliary arteries (SPCA). At the same time following indexes were estimated: Peak Systolic Velocity (PSV, cm/sec), End Diastolic Velocity (EDV, cm/sec), Average Blood Velocity (ABV, cm/sec), Index of peripheral vascular resistance (R1, M ± m). Results. After the end of hospitalization of patients with AION, more favorable shifts in indexes of hemodynamic in SPCA were reached in patients of main group of research that authentically exceeded the similar data obtained at patients in the control group. Improvement of blood flow of ON was followed by positive changes of thickness of the retinal nerve fiber layer and condition of disk ON. To the final stage of researches (12 months from beginning of treatment) according to degrees of functional disorders severity in the main group of patients prevailed I (14 patients, 60%), less often II degrees (9 patients, 40%) of optic nerve atrophy and absented patients with III degrees of defeat of ON. Among patients of control group II–III degree optic nerve atrophy (12 patients, 60%) met more often, less often I degrees (8 patients, 40%). Conclusion. The conducted research showed that at patients with AION receiving sub-Tenon's infusions of MP more significant favorable functional results were reached thanks to increase of indicators of blood flow in SPCA: PSV — on 24.5%, EDV — on 16.2%, ABV — on 32.2% that significantly exceeds similar data at patients in control group with traditional methods of MP injections.